WORK LOAD CONNECTION WITH WORKING STRESS WORK IN CENTRAL SURGICAL INSTALLATION - Honesty Diana Morika (STIKes Payung Negeri Pekanbaru, 2018)
Stress on the nurse can be caused by various factors, such as workload. The workload of nurses in the hospital includes the physical and mental workload. According to the results of research conducted by the National Nurses Association of Indonesia (2006) there are 50.9% of nurses experiencing work stress. The purpose of the study to determine the relationship with the workload of work stress nurses in Central Surgery Installation Hospital General Hospital Dr. M. Djamil Padang in 2017. Type of analytic research with Cross Sectional Study design that has been implemented in Central Surgery Installation of Dr. M. Djamil Padang. The population of the study were all nurses who served in the Central Surgery Installation of Dr.M. Djamil Padang, amounting to 34 people with a sample of 34 people. Data analysis was done by univariate analysis and bivariate analysis using Chi-Square statistical test. The result of the research was more than half (61,8%) of the respondent had stress at the nurse. More than half (58.8%) of respondents have a heavy workload on work stress on the Nurse Implementing. There is a significant relation between workload and work stress of Nurse Executor in Central Surgery Installation. The conclusion is there is a meaningful relationship between workload with work stress Nurse Implementation in Central Surgery Installation RSUP Dr. M. Djamil Padang, it is expected that the hospital should pay more attention to the welfare of the nurses with work load and higher work risk in the hope that the workload is felt not too heavy so as not to cause work stress on the Nurse Implementation in Central Surgery Installation. M. Djamil Padang